An Electrochemical Synthesis Approach for Tetrasubstituted Olefins. Issue 7 (24th May 2019) - Lu, Fangling; Yuan, Yong
Abstract : We herein developed a new electrochemical synthesis approach for tetrasubstituted olefins .